Pemberdayaan Lembaga Adat Desa Dalam Melestarikan Adat Istiadat Guna Membantu Dalam Penanggulangan Kemiskinan di Desa Wonokitri Kecamatan Tosari dan Desa Ngadirejo Kecamatan Tutur Kabupaten Pasuruan - Edy Suprianto (Penerbit STKIP PGRI Bangkalan, 2025)
Based on the Regulation of the Minister of Home Affairs No. 18 of 2018 as stated in Article 11 and Article 14 concerning Village Community Institutions and Village Customary Institutions, it is explained that the Village Customary Institution, hereinafter abbreviated as LAD, is an institution that carries out customary functions and is part of the original structure of the Village that grows and develops on the initiative of the Village community. The purpose of LAD is basically to be a partner of the Village Government in increasing community participation, as a process of Village development, and ensuring the smooth running of Village Government services. The focus of this research is related to the LAD empowerment strategy in preserving customs and poverty alleviation in the research location. This research uses a qualitative descriptive approach, where in qualitative descriptive research aims to obtain information about existing conditions. In other words, qualitative descriptive research seeks to describe, record, analyze, and interpret conditions that currently occur or exist. The results of this study are that the strategy that can be implemented is to use the Asset Based Community Development (ABCD) theory with the Appreciative Inquiry (AI) type using the 4-D cycle, namely the discovery, dream, design, and destiny models